2013
DOI: 10.9790/7388-0325560
|View full text |Cite
|
Sign up to set email alerts
|

Make the laboratory work meaningful through Concept maps and V Diagram

Abstract: This paper describes how these tools (concept map and V diagram)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
0
6
0
2
Order By: Relevance
“…Moreover, from a psychological perspective, the knowledge map was found to decrease students' anxiety regarding learning materials and to increase their motivation (Hall and OʹDonnell 1996). In addition, it has been found that the use of knowledge maps improves students' performance and in the physical science laboratories (Safdar et al 2013). All of these findings are consistent with schema theory and have inspired the authors to hypothesize that knowledge maps will be equally effective in open learning environments and will provide the required support for learners.…”
Section: Fig 1 Simple Illustration Of the Main Components Of Knowledmentioning
confidence: 99%
“…Moreover, from a psychological perspective, the knowledge map was found to decrease students' anxiety regarding learning materials and to increase their motivation (Hall and OʹDonnell 1996). In addition, it has been found that the use of knowledge maps improves students' performance and in the physical science laboratories (Safdar et al 2013). All of these findings are consistent with schema theory and have inspired the authors to hypothesize that knowledge maps will be equally effective in open learning environments and will provide the required support for learners.…”
Section: Fig 1 Simple Illustration Of the Main Components Of Knowledmentioning
confidence: 99%
“…Assessment of laboratory work by direct use of concept mapping is not a common practice in Kenya. During laboratory work, students carry out activities producing a set of results which are not commonly related back the conceptual framework that underpins the experimental work in a meaningful way (Safdar et al, 2013) Meaningful learning takes place when learners are able to recognise interrelationships between different segments of the concepts and being able to join the segments and create meaning (Ruiz-Primo, 2004;Ituma, 2015). The commonly used chemistry assessment methods which are mainly multiple choice and short answer questions are good in testing concepts but have no ability of showing learner understanding of relationships or even broader applications of the concepts (Soika & Reiska, 2014).…”
Section: The Use Of Concept Mapsmentioning
confidence: 99%
“…The relationship between the activities and concepts intended to be learnt is however low (Ituma, 2015). In order to make learning meaningful in the laboratories, it is important that learners are able to establish relations between theory and practice as well as with their everyday experiences (Safdar, et al 2013). It is of vital importance to link the concepts learnt with the activities carried out in the laboratory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It provides many opportunities for students to talk and write about science. With a little thought and planning on the part of the students, laboratory activities can be the basis for building communication and problem solving skills (Safdar, Hussain, Shah & Tasnim, 2013). However, traditional approaches based on deduction do not help students learn science lessons in laboratories at all.…”
Section: Introductionmentioning
confidence: 99%